KAJIAN FISIOLOGI TANAMAN KEDELAI PADA BERBAGAI KEPADATAN GULMA TEKI DALAM KONDISI CEKAMAN KEKERINGAN - Purwanto Purwanto; T. Agustono (Universitas Tadulako, 2010)
The aim of this research was to study the effect of drought stress and weeds density to the physiology of soybean plant. The research was a pot experiment arranged in a Randomized Completely Block Design (RCBD). Treatment factors were drought stress and initial population density of weeds. The drought stress treatments consisted of three levels, i.e.: field capacity, 60% field capacity and 40% field capacity water content. The density of weeds comprised 5 densities, i.e.: 0, 5, 10, 15 and 20 tubers per pot. Variables observed were leaf area, number of leaves, transpiration rate, photosynthesis rate, stomata width, number of chlorophylls, dry weight of above ground plant. Data were analyzed by F test, followed by Honestly Significant Difference (HSD) at error level of 5 %. The results showed that water stress at 60% of field capacity decreased the stomata width to 33.14%, 10.45% transpiration rate, and 7.73% chlorophylls contents. The initial population density of weeds decreased the stomata width up to 17.14%. The interaction effect of drought stress and weeds density reduced the leaf area to 35.70% and 20.41 % of photosynthesis rates.